2022
DOI: 10.1111/1759-7714.14340
|View full text |Cite
|
Sign up to set email alerts
|

The airway microbiota of non‐small cell lung cancer patients and its relationship to tumor stage andEGFRgene mutation

Abstract: Background: Accumulating studies have suggested the airway microbiota in lung cancer patients is significantly different from that of healthy controls. However, little is known about the relationship between airway microbiota and important clinical parameters of lung cancer. In this study, we aimed to explore the association between sputum microbiota and lung cancer stage, lymph node metastasis, intrathoracic metastasis, and epidermal growth factor receptor (EGFR) gene mutation. Methods: The microbiota of sput… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…Additionally, we did not find a marked difference between the two groups in the taxonomic composition (beta diversity). Different studies reported different alpha and beta diversity results in lung cancer, including increased alpha diversity [ 15 , 16 ], decreased alpha diversity [ 17 , 18 ], increased beta diversity [ 19 , 20 ], decreased beta diversity [ 17 , 21 , 22 ], and no diversity changes [ 21 , 23 ]. Overall, these results indicate that there is still no definite consensus about the diversity of the lung microbiome composition in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we did not find a marked difference between the two groups in the taxonomic composition (beta diversity). Different studies reported different alpha and beta diversity results in lung cancer, including increased alpha diversity [ 15 , 16 ], decreased alpha diversity [ 17 , 18 ], increased beta diversity [ 19 , 20 ], decreased beta diversity [ 17 , 21 , 22 ], and no diversity changes [ 21 , 23 ]. Overall, these results indicate that there is still no definite consensus about the diversity of the lung microbiome composition in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…During the early stage (stage I–II) of NSCLC, Firmicutes, Bacillus , and Actinobacteria were significantly enriched. Actinobacteria were remarkably enriched during the late stage (stage III–IV) [14]. Additionally, the species of bacteria that are observed in lung cancer depend on the sampling site and the classification of pathology.…”
Section: The Microbiome In Lung Cancer Patientsmentioning
confidence: 99%
“…Epidermal growth factor receptor (EGFR) mutation is a major prognostic factor in LUAD patients. Numerous studies have shown that EGFR mutation is positively correlated with the abundance of Bacteroides , Parvimonas , and Actinobacillus [14]. One recent study indicated that treponema and fibrillar factor could be used as biomarkers of lung cancer in tests of saliva and BALF samples [44].…”
Section: The Microbiome In Lung Cancer Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main attention has been devoted to the correlation of EGFR status and lung microbiome, and experimental reports already suggested that in bronchoscopy-obtained NSCLC samples, the detection of EGFR-mutant cells has been correlated with the abundance of rare species, such as Rhizopus oryzae, Natronolimnobius innermongolicus, Staphylococcus sciuri [18]. The genus Parvimonas has been documented to be significantly enriched in EGFR-mutant adenocarcinomas as well [53]. Similarly, in colorectal cancer, the occurrence of somatic mutations affecting the KRAS oncogene has been significantly associated with the composition of intestinal flora, namely Roseburia, Parabacteroides, Metascardovia, Staphylococcus and Bacillales, thus promoting cancer onset [54].…”
Section: Genetic Signatures On Microbiota and Effect Of Microbiota On...mentioning
confidence: 99%